Media Sistem Peredaran Darah Hewan dan Manusia Dilengkapi Augmented Reality Kelas V Sekolah Dasar - Leny Suryaning Astutik; Markus Diantoro; Sentot Kusairi (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The circulatory system and animals are important materials to learn in elementary school. The purpose of this study is to produce SIPERDA media equipped with augmented reality for the fifth grade of Malang Regency Primary School which is effective, valid, and practical. The development of SIPERDA uses the ADDIE model. The results showed the average for validity from media experts, material experts, and learning experts was 87.2% with the category